SAT-097 Early Adiposity Rebound in Youth with Congenital Adrenal Hyperplasia Predicts Childhood Obesity and Adiposity in Adolescence - Bhullar, Gagandeep (J Endocr Soc, 2020)
Purpose: Youth with classical Congenital Adrenal Hyperplasia (CAH) due to 21-hydroxylase deficiency have an increased prevalence of obesity, abdominal adiposity, and fat mass compared to unaffected youth. As well, CAH youth in the United Kingdom (UK) have been found to have an earlier adiposity rebound (AR; rise in BMI corresponding to increased adipocyte size and number) at 1.7 years old, three years earlier than the general UK population. In unaffected youth, an earlier AR is predictive of obesity in adolescence. Our objective was to further understand the relationships between AR, weight status, and disease factors inherent to CAH in pediatric patients at our United States (US) center. Methods: In 45 youth with classical CAH, weight-for-length (kg/cm; if <2 yr) percentiles or BMI (kg/m(2); if ≥2 yr) Z-scores were calculated every 6 months between the ages of 1 and 7 years, and at the patient’s last clinic visit. The cubic polynomial method was used to determine age at AR, located at the nadir before the second rise in the model. BMI-Z at the last clinic visit (12.6±3.8 yr) was used to classify final weight status as lean (Z<2) or obese (Z≥2). AR, and weight-for-length percentile at 1 yr, were analyzed for prediction of BMI-Z at 7 yr. Additionally, in a subset of 21 CAH youth enrolled in prior studies, total body fat and trunk fat (DXA), as well as abdominal subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT; single-slice CT or 3-T MRI at the level of the umbilicus) were cross-sectionally measured. Other CAH factors assessed in all youth included: glucocorticoid dose at AR, 17OHP at newborn diagnosis, and average bone age SD from clinical x-rays. Mann-Whitney U tests and Pearson correlations were used to assess group differences and associations. Simple linear regressions were used to predict childhood obesity and adolescent adiposity. Data are presented as mean±SD. Results: Age at AR for CAH youth was 3.1±1.4 yr, which is earlier than the normative US population (5.5 yr). Stratifying youth by weight status at their last clinic visit, age at AR was earlier in obese (2.5±1 yr, n=23) versus lean (3.7±1.6 yr, n=22; p<0.01) youth. AR strongly predicted BMI-Z at 7 yr (R= -0.65, β= -0.27, p<0.001) whereas weight-for-length percentile did not (R=0.22, p=0.14). AR was negatively correlated with total body fat (R= -0.58, p<0.01), trunk fat (R= -0.60, p<0.01), and abdominal SAT (R= -0.60, p<0.01), but not with VAT (R= -0.24, p=0.3). There were no associations between AR and glucocorticoid dose or newborn 17OHP. However, AR was negatively correlated with bone age SD (R= -0.37, p=0.05). Conclusion: Youth with CAH at our center exhibited an earlier AR by two years compared to the normative US population. This earlier AR was predictive of obesity in childhood, as well as increased total body fat and central adiposity in adolescence. Further study of disease-specific factors such as genotype in CAH are merited.